ENHANCING STUDENTS' SPEAKING SKILL BY USING THINK PAIR SHARE COLLABORATED WITH VIDEO AT SMPN 2 LUBUKLINGGAU - Dwi Maulianto Dwi (Teaching and General Education Studies, 2025)
This study aims to determine the completeness of learning outcomes of the effectiveness the Think Pair Share (TPS) strategy combined with video in improving students’ speaking skills at SMPN 2 Lubuklinggau. A pre-experimental method was applied using one group pre-test and post-test design, involving 38 eighth-grade students. The sampling technique used was random sampling technique. The prerequisite analysis technique uses normality test while the hypothesis used a sample t-test. The pre-test showed an average score of 58.57 with a standard deviation of 10.47, where only 29% of students reached the "Mastered" level. After four sessions of treatment using TPS with video, the post- test average increased to 70.89 with a standard deviation of 7.39, and 58% of students achieved the "Mastered" qualification. the results of these tests, it was obtained that tcount = 4.54, while with a significant level of α = 0.05, the ttable obtained was 1.687. This indicates that tcount > ttable, which is 4.54 > 1.687. Thus it can be said that Ha is accepted and Ho is rejected, the hypothesis proposed by this study can be accepted as true. So it can be concluded, that the application of the Think Pair Share strategy in speaking Learning of grade VIII.9 at SMPN 2 Lubuklinggau students is significantly completed.